Next-generation sequencing testing in children with epilepsy reveals novel clinical, diagnostic and therapeutic implications - Krygier, Magdalena; Pietruszka, Marta; Zawadzka, Marta; Sawicka, Agnieszka; Lemska, Anna; Limanówka, Monika; Żurek, Jan; Talaśka-Liczbik, Weronika; Mazurkiewicz-Bełdzińska, Maria (Frontiers in Genetics, 2024)
Introduction: Epilepsy is one of the commonest diseases in children, characterized by extensive phenotypic and genetic heterogeneity. This study was conducted to determine the diagnostic utility and to identify novel clinical and therapeutic implications of genetic testing in pediatric patients with epilepsy.Methods: Large multigene panel and/or exome sequencing was performed in 127 unrelated Polish and Ukrainian patients with suspected monogenic epilepsy. Diagnostic yields were presented for five phenotypic subgroups, distinguished by seizure type, electroencephalographic abnormalities, anti-seizure treatment response, and neurodevelopmental deficits.Results: A definite molecular diagnosis was established in 46 out of 127 cases (36%).Alterations in six genes were detected in more than one patient: SCN1A, MECP2, KCNT1, KCNA2, PCDH19, SLC6A1, STXBP1, and TPP1, accounting for 48% of positive cases. 4/46 cases (8.7%) were mosaic for the variant. Although the highest rates of positive diagnoses were identified in children with developmental delay and generalized seizures (17/41, 41%) and in developmental end epileptic encephalopathies (16/40, 40%), a monogenic etiology was also frequently detected in patients with solely focal seizures (10/28, 36%). Molecular diagnosis directly influenced anti-seizure management in 15/46 cases.This study demonstrates the high diagnostic and therapeutic utility of large panel testing in childhood epilepsies irrespective of seizure types. Copy number variations and somatic mosaic variants are important disease-causing factors, pointing the need for comprehensive genetic testing in all unexplained cases. Pleiotropy is a common phenomenon contributing to the growing phenotypic complexity of single-gene epilepsies.